Emerging Role of PET in the Diagnosis and Staging of Lung Cancer - Geoffery Coates; Stephen J Skehan (Canadian Respiratory Journal)
Positron emission tomography (PET) with 18F-fluoro-2-deoxyglucose (FDG) has recently emerged as a practical and useful imaging modality in patients with lung cancer. Malignant tumours demonstrate increased uptake of FDG, a positron-emitting radiopharmaceutical. This increased FDG uptake in tumours can be seen using PET. FDG PET has much higher accuracy than other imaging modalities for the differentiation of benign and malignant lung nodules. The sensitivity of PET is 96% and the specificity 77% for diagnosing malignant nodules. PET is also more accurate than computed tomography (CT) for staging mediastinal nodal involvement (sensitivity 89%, specificity 94%). While CT relies on an arbitrary anatomical cutoff of 1 cm to diagnose malignant nodes, which may simply be enlarged due to inflammation, PET can accurately diagnose metastases in nodes smaller than 1 cm. Several studies have shown significantly better staging of distant metastases with FDG PET than with traditional techniques such as bone scanning. Differentiation of recurrent disease from scar tissue in the postoperative patient is often difficult with CT or magnetic resonance imaging. The low uptake of FDG in scar tissue allows reliable differentiation between scar tissue and a recurring tumour with PET. Early studies suggest a promising role for PET in the evaluation of response to chemotherapy. This may allow treatment to be changed after only one course of chemotherapy, instead of waiting for anatomical disease progression to become obvious clinically or with CT. Finally, significant improvements in cost effectiveness have been demonstrated when FDG PET is added to the preoperative work-up of patients with lung cancer.